Pengaruh Kualitas, Harga, Citra Merek, Kelompok Rujukan Terhadap Keputusan Konsumen Membeli Terios - Hasan, Youlanda (JURNAL RISET BISNIS DAN MANAJEMEN, 2013)
Manado city is one of cities in Indonesia that grows rapidly and has good economic growth that business people to introduce their products target it. One company that introduce its products is Daihatsu Terios. Daihatsu Terios is an SUV car production. The objective of this research is to analyze the influence of product quality, price competitiveness, brand image, and reference group on consumer purchase decision of Daihatsu Terios car in Manado. Based on partial analysis, it shows that product quality, price, brand image, and reference group influence consumer purchase decision of Daihatsu Terios car in Manado. It means, according to consumers, product quality, price competitiveness, brand image, and reference group are considered important when purchase Daihatsu Terios car. Based on simultaneous analysis, product quality, price, brand image, and reference group influence consumer purchase decision of Daihatsu Terios car in Manado